2015
DOI: 10.1016/j.cell.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A XEN-like State Bridges Somatic Cells to Pluripotency during Chemical Reprogramming

Abstract: Somatic cells can be reprogrammed into pluripotent stem cells (PSCs) by using pure chemicals, providing a different paradigm to study somatic reprogramming. However, the cell fate dynamics and molecular events that occur during the chemical reprogramming process remain unclear. We now show that the chemical reprogramming process requires the early formation of extra-embryonic endoderm (XEN)-like cells and a late transition from XEN-like cells to chemically-induced (Ci)PSCs, a unique route that fundamentally di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
246
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 225 publications
(271 citation statements)
references
References 30 publications
14
246
2
2
Order By: Relevance
“…The study published by Zhao et al [5] now confirms that CiPSCs are derived via a XEN-like state, which allowed them to enhance the efficiency of the chemical-induced reprogramming by dissection of the cell fate transitions. They first observed that CiPSCs emerged from epitheloid colonies that expressed XEN markers and knocking these markers down hampered CiPSC formation.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…The study published by Zhao et al [5] now confirms that CiPSCs are derived via a XEN-like state, which allowed them to enhance the efficiency of the chemical-induced reprogramming by dissection of the cell fate transitions. They first observed that CiPSCs emerged from epitheloid colonies that expressed XEN markers and knocking these markers down hampered CiPSC formation.…”
mentioning
confidence: 79%
“…Although the past decade has seen methodological improvements, generation of iPSCs still requires genetic manipulation that hinders their therapeutic application. The chemical cocktail developed by Zhao et al [5] of Deng's group circumvents this problem.…”
mentioning
confidence: 99%
See 3 more Smart Citations